EVOLUTIONARY HISTORY OF VERTEBRATES AND IT’S SKELETAL MORPHOLOGY - RITA JAISWAL (International Journal of Multidisciplinary Research and Studies, 2020)
The vertebral column, sometimes known as the backbone, is one of the most distinguishing characteristics of vertebrates. This structure is made up of a number of tiny bones known as vertebrae. These vertebrae are joined to one another by joints, and the space between them is occupied by discs that are both soft and flexible. Because of this, vertebrates are able to quickly digest information and respond to stimuli in a coordinated manner. In order to efficiently ventilate these lungs by the movements of the cranial ribs, these tejus have developed a posthepatic septum from the embryonic septum transversum and the cranial mesosalpinx. This prevents the intestines from being sucked into the cranial body cavity during strong inspirations. Certain species of tiny lizards exhibit an additional kind of differentiation of their paired unicameral lungs by generating caudal dilatations that are not associated with respiration. During normal breathing, these dilatations are compressed, but they become inflated in defensive situations by taking in the maximum amount of air possible. For instance, several members of the iguanid genus Sauromalus do this so that they may anchor themselves in rock crevices. In lizards belonging to a number of different families that have a discernible extension of the trunk, the lungs have more or less extended caudal non-respiratory dilatations that are, for the most part, formed asymmetrically. These dilatations result in a significant increase in the volume of the lungs and, as a consequence, the total capacity of the body cavity. This results in increased cross-sectional dimensions of the trunk and the ribs, which in turn results in improved mobility of the trunk.